2022
DOI: 10.3390/jcm11072008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on In-Patient Treatment of Peripheral Artery Disease in Germany during the First Pandemic Wave

Abstract: Patients with peripheral artery disease (PAD) belong to a vulnerable population with relevant comorbidity. Appropriate care and timely treatment are imperative, but not readily assured in the current pandemic. What impact did the first wave have on in-hospital treatment in Germany? Nationwide healthcare remuneration data for inpatient care of the years 2019 and 2020 were used to compare demographic baseline data including the assessment of comorbidity (van Walraven score), as well as the encoded treatments. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This finding might be explained by the above-mentioned reallocation of in-hospital capacities with corresponding reduction in surgical capacities and thus an increase in transarterial treatments. Additionally, the number of admissions without liver-directed treatments decreased, potentially reflecting a more focused admission of patients that required treatment as was also observed in other diseases such as peripheral artery disease [53].…”
Section: Discussionmentioning
confidence: 64%
“…This finding might be explained by the above-mentioned reallocation of in-hospital capacities with corresponding reduction in surgical capacities and thus an increase in transarterial treatments. Additionally, the number of admissions without liver-directed treatments decreased, potentially reflecting a more focused admission of patients that required treatment as was also observed in other diseases such as peripheral artery disease [53].…”
Section: Discussionmentioning
confidence: 64%
“…To flatten the curve of infections, the German Ministry of Health introduced lockdown measures and social distancing in March 2020. In previous studies, a decline was reported in hospitalization of patients with acute medical conditions (e.g., ischaemic stroke or vascular diseases) during the periods of lockdown and socual distancing in 2020 and 2021 [7–11].…”
Section: Introductionmentioning
confidence: 99%